2021
DOI: 10.1007/s10856-020-06471-w
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of different dental resin-cements on human cell lines

Abstract: Adhesive resin-cements are increasingly used in modern dentistry. Nevertheless, released substances from resin materials have been shown to cause cellular toxic effects. Disc-shaped specimens from 12 different resin cements and one conventional zinc phosphate cement were prepared and used for direct stimulation of five different human cell lines via transwell cell culture system or in an indirect way using conditioned cell culture media. Cytotoxicity was determined using LDH and BCA assays. All tested cements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The permeation of cell membranes was enhanced using 1× Triton, and non-specific binding was blocked using 1% bovine serum albumin. Finally, the wells were stained with rhodamine–phalloidin or DAPI and washed three times with 1× PBS prior to image acquisition and analysis using an Axio Observer Z1 microscope …”
Section: Methodsmentioning
confidence: 99%
“…The permeation of cell membranes was enhanced using 1× Triton, and non-specific binding was blocked using 1% bovine serum albumin. Finally, the wells were stained with rhodamine–phalloidin or DAPI and washed three times with 1× PBS prior to image acquisition and analysis using an Axio Observer Z1 microscope …”
Section: Methodsmentioning
confidence: 99%
“…As biomaterial scaffolds are in vivo implants that need to be retained in vivo for a period of time, some conventional performance parameters need to be considered first ( Table.2 ). Safety indicators such as biocompatibility, cytotoxicity, and immunogenicity should be the key consideration ( Marin et al, 2020 ; Zhu et al, 2020 ; Diemer et al, 2021 ). It is a prerequisite for biomaterials to function without causing local or even systemic adverse reactions in vivo .…”
Section: Biomaterials Design and Macrophage Regulationmentioning
confidence: 99%
“…Ensure the safety of the implantMarin et al (2020) CytotoxicityEnsure the safety of the implantDiemer et al (2021) Immunogenicity Ensure the safety of the implantGao et al (2021) Biodegradablity Provide proper support and space for new tissueMiao et al (2021) Antibacterial property Ensure the safety of long-term implantation and assist in the treatment of possible co-infection of bone defectsWu et al (2021) Parameters to regulate macrophageDegradation product Influence macrophage phenotype and secretion Chen et al (2014) Pore size Influence macrophage morphology, infiltration and polarization Tylek et al (2020); Li et al (2022) Substrate stiffness Influence macrophage migration, polarization and phagocytosis Sridharan et al (2019) Surface roughness Influence macrophage attachment and polarization Wang et al (2018) Surface wettability Influence macrophage phenotype and secretion Lv et al (2018) Material topography Inflience macrophage attachment, morphology, polarization and secretion Chen et al (2010) 3D structure Influence macrophage morphology, fusion, infiltration and polarization Jiang et al (2016). Provide a microenvironment close to the body Material group charge Influence macrophage polarization and osteogenic differentiation Mao et al (2022) Material group chirality Influence macrophage phenotype and secretion Jiang et al (2022) Physical stimulation Influence macrophage morphology, migration, polarization and secretion Hoare et al (2016); Wosik et al (2018) Frontiers in Bioengineering and Biotechnology frontiersin.org absorbed by macrophages or affect the local microenvironment.…”
mentioning
confidence: 99%
“…Nevertheless, released substances from resin materials have been shown to cause toxic cellular effects. Diemer et al [38] investigated the effect of resin-cements against different cell-lines and reported that all their tested resin cements significantly reduced cell viability of human cells especially, osteoblastic cells demonstrated a tremendous increase of cytotoxicity after cement exposure. The authors suggested that the wide use of resin cement in every clinical situation should be scrutinized.…”
Section: Health Impact Of Conventional Polymer-based Materials In Obstetrics and Gynecologymentioning
confidence: 99%